Glass house : shattering the myth of evolution - Ham, Ken; Hodge, Bodie (Green Forest, AR : Master Books, 2019)
Evolutionists try to convince others that their evolutionary world is built on solid foundations, while they distract us from the fact that their house is only made of glass and the glass is breaking.
Keywords: Creationism; Evolution; Intelligent design (Teleology); Evolution -- Religious aspects -- Christianity; Creationism; Evolution; Intelligent design (Teleology); Evolution -- Religious aspects -- Christianity